(untitled) (Acta Polytechnica CTU Proceedings, 2018)
Coated cladding materials are considered as a near-term concept for so-called Accident Tolerant Fuel materials. Their behavior in accidental conditions is mainly studied around the world, however, they need to survive in-reactor normal operation before reaching theoretical accidental conditions. An out-of-pile experiment was designed to study accelerated inward thermal creep and outward displacement of a cladding that occurs after pellet-cladding interaction. Four different materials deposited by the cold-spray technique were studied as well as the reference uncoated one. The results confirm theoretical prediction that due to a mismatch between the fundamental physical properties of each layer, high stresses will build up and the plastic strains expected will lead to coating cracking.